Studies on the effects of cephradine and colibacellosis on immunological status of broiler chicken vaccinated with newcastle virus vaccine - Elkomy, Ashraf; Aboubakr, Mohamed; Emam, Elsayed; Kassem, Mohammed (International Journal of Pharmacology and Toxicology, 2019)
The present study was carried out using 100, one-day old broiler chicks to evaluate the immunological status of broiler chicks vaccinated with Newcastle virus vaccine and infected with E coli and treated by cephradinee.At day 15th of age, broilers chicks were divided into 4 equal groups (25 chicks in each). 1st group, healthy non infected non treated broilers (control group). 2nd, 3rd and 4th groups expermintally infected with E. coli was done at 15th day of age. 2nd group infected, non treated broilers, 3rd group infected broilers and vaccinated with Newcastle disease virus vaccine, 4th group infected broilers vaccinated with Newcastle vaccine and received 20 mg/kg b.wtcephradinee in drinking water daily for 5 consecutive days. At 1st, 10th and 20th day post administration, blood samples were collected for determination cellular and humeral immune response. Infected broilers with E coli only or infected broilers and vaccinated display significant increase in leukocyte, heterophils, phagocytic activity, phagocytic index, killing percentage, nitric oxide, lysozyme activity and gamma globulin. Beside significant decrease in lymphocyte, serum total protein, albumin, total globulin, A/G ratio and HI titer coupled with insignificant decrease in esinophils, basophils and monocyte, beta globulin associated with insignificant increase in alpha globulin allover experimental period post vaccination when compared with control broilers. Vaccinated-Infected broilers that received 20 mg/kg b.wtcephradine daily for five consecutive days revealed significant increase in leukocyte, heterophils, phagocytic activity, phagocytic index, killing % and gamma globulin at 1st day post treatment coupled with insignificant increase at 10th and 20th day post treatment. In-addition to significant decrease in serum total protein, albumin, total globulin A/G ratio and HI associated with non significant decrease in esinophils, basophils, monocyte,beta globulin and non significant increase in nitric oxide, lysozyme activity and alpha globulin allover the experiment when compared with control broilers. It could be concluded that, colibacillosis in broiler chickens and cephradine induced some adverse effects on immunological status of broiler chickens. Therefore, itâ€™s important not vaccinated broiler during colibacelosis or using cephradine in treatment.Â Â